The effect of some storage methods on the quality and shelf-life of some cultivars of white yam (Dioscorea rotundata) variety - Addae, Alphonse Kwesi (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Philosophy in Postharvest Technology,